Optimization of biodiesel production from waste cooking oil using α-Fe2O3/HAP catalyst via simultaneous esterification-transesterification reaction. Issue 2 (15th June 2022) - Widayat, W.; Hadiyanto, Hadiyanto; Buchori, Luqman; Prameswari, Jedy; Jeksen, Rio Michael; Cahyonugroho, Jovita
ABSTRACT: The study aimed to optimize a waste-cooking oil-based biodiesel production process using α-Fe2 O3 /Hydroxyapatite (HAP) catalyst from natural iron sand and phosphate rocks. The parameters investigated in this study were reaction temperature, methanol:WCO molar ratio, and catalyst weight. Response surface methodology (RSM) with central composite design (CCD) was used to design the experiment, and a model in the form of a quadratic equation was later generated based on the investigated parameters and the observed biodiesel yield response. The model was subjected to ANOVA analysis to determine its validity and the influence of the investigated parameters on the observed response. The results showed that the catalyst weight was the only parameter significantly influencing the biodiesel yield, although the reaction temperature was concluded to be borderline significant. The optimal reaction condition suggested was 70°C reaction temperature with 3.68 %w/w catalyst weight and 10.47 mol/mol methanol:WCO molar ratio to achieve 93.96% biodiesel yield.